Macrophage Infiltration into Subcutaneous Adipose Tissue is Associated with Local Levels of 11BHSD1 - Korkmaz, H.; Bozdag, Z.; Akarsu, E.; Tarakcioglu, M.; Ulusal, H.; Gökalp, M. A. (Experimental and Clinical Endocrinology & Diabetes, 2016)
The present study aimed to evaluate the infiltration of macrophages in form of crown-line structures (CLS) in subcutaneous adipose tissue (SAT) of obese individuals, and to investigate the effect of these on both metabolic parameters and adipose tissue 11-beta-hydroxysteroid dehydrogenase type 1 (11BHSD1) enzyme levels. A total of 53 obese (10 men, 43 woman) enrolled in the study. Body mass index (BMI), waist circumference (WC), hip circumfrence, and systolic (SBP) and diastolic blood pressures (DBP) of all subjects were recorded. Insulin resistance was determined using the homeostasis model assessment (HOMA). The concentration of SAT, tumor necrosis factor (TNF)-α, interleukin (IL)-6, 11BHSD1 were performed by enzyme-linked immunosorbent assay (ELISA) method. The infiltration of macrophages in form of CLS in adipose tissue were determined using cell-specific stains against CD68. There was no significant difference between the CLS+group and the CLS– group in terms of age, gender, BMI, WC, waist-to-hip circumference ratio (WHR), SBP and DBP levels. Fasting plasma glucose (FPG), HOMA-IR, insulin and SAT TNF-α levels were higher in the CLS+group compared to the CLS− group. FPG and SAT TNF-α levels were significantly higher in participants with high CLS density compared to participants with low density CLS. SAT 11BHSD1 levels was significant higher in the CLS+group compare to the CLS− group and in the high CLS density group compared to the low density group. In conclusion, the infiltration of macrophages in the form of CLS in SAT is associated with increased 11BHSD1 levels. It may be an important mechanism in the development of metabolic disorders.
Keywords: crown-line structures; metabolic syndrome; 11BHSD1; subcutaneous adipose tissue